Communications: Wireless in Developing Countries and Networks of the Future Third IFIP TC 6 International Conference, WCITD 2010 and IFIP TC 6 International Conference, NF 2010, Held as Part of WCC 2010, Brisbane, Australia, September 20-23, 2010. Proceedings - Pont, Ana.; Pujolle, Guy.; Raghavan, S. V.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This book constitutes the refereed proceedings of the Third IFIP TC 6 International Conference on Wireless Communications and Information Technology for Developing Countries, WCITD 2010 and the IFIP TC 6 International Network of the Future Conference, NF 2010, held as part of the 21st World Computer Congress, WCC 2010, in Brisbane, Australia, in September 2010. The 7 revised full papers presented at WCITD were carefully reviewed and selected from 17 submissions. They cover various topics in wireless and mobile communication, wireless and mobile networks and information technologies and systems and focus on innovative technical research. The 15 revised full papers presented at NF were carefully reviewed and selected from numerous submissions. They deal with important paradigms for the post-IP generation: new architectures, knowledge and piloting planes, network virtualization, green technologies, sensor networks, mobile and wireless networks, and strong security.
WCITD 2010 -- Preface -- Semantic Clustering in Wireless Sensor Networks -- C3TO: A Scalable Architecture for Mobile Tutoring over Cell Phones -- Wireless Mesh Networks for Infrastructure Deficient Areas -- Establishing Low Cost Aquatic Monitoring Networks for Developing Countries -- Infrastructure and Business Model for Universal Broadband Access in Developing Regions: The Ceara State Digital Belt -- ICT Driven Knowledge Management in Developing Countries: A Case Study in a Chinese Organisation -- Technical ICTD - A User Centered Lifecycle -- NF 2010 -- Preface -- An Introduction to the Network of the Future -- Future Internet Is by Ethernet -- On the Way to a Theory for Network Architectures -- Green Network Planning Model for Optical Backbones -- Internet Sensor Grid: Experiences with Passive and Active Instruments -- Data-Driven MAC for Efficient Transmission of Spatially Correlated Data in WSNs -- Leveraging Trusted Network Connect for Secure Connection of Mobile Devices to Corporate Networks -- OpenFlow and Xen-Based Virtual Network Migration -- Virtual Network Urbanization -- New Routing Paradigms for the Next Internet -- End-to-End Performance Evaluation of Interconnected Optical Multi-ring Metropolitan Networks -- A Relative Bandwidth Allocation Method Enabling Fast Convergence in XCP -- On the Interest of Introducing Randomness in Ad-Word Auctions -- The Role and Future Challenges of Wireless Communication Networks for Cooperative Autonomous City Vehicles -- Performance Analysis of User-Centric Network Selection and Network-Centric Resource Allocation Approaches in Wireless Networks.
Keywords: Computer science; Computer Communication Networks; Software engineering; Computer software; Information storage and retrieval systems; Information systems; Computer Science; Computer Communication Networks; Information Systems Applications (incl.Internet).; Information Storage and Retrieval; Computers and Society; Software Engineering; Algorithm Analysis and Problem Complexity